The Effect of Silver Diamine Fluoride and Fluoride Varnish on Roughness of Primary Teeth Enamel (An In Vitro Study) - Sura A. Abdil-Nafaa; Aisha A. Qasim (University of Mosul, College of Dentistry, 2020)
Aims: The study aimed to evaluate and compare the effect of fluoride varnish and silver diamine fluoride solution on surface roughness of enamel of primary teeth in vitro study. Materials and methods: A total of (150) primary anterior teeth were used. Enamel blocks were prepared and divided into three groups: Fluoride varnish group n(50), silver diamine fluoride groupn(50), and the control group of deionized water n(50). PH cycle completed at one day and repeated for 10 days. Specimens were kept in demineralizing solution for 3 hours and remineralizing solution for 20 hours. All specimens were washed in deionized water between solutions and placed in artificial saliva for 30 minutes at the end of the demineralization and remineralization process. Surface roughness was measured before and after PH cycle. Results: There was no significant difference between groups before PH cycle while at the end of PH cycle, groups showed highly significant difference at p ≤ 0.01. Also, silver diamine fluoride had the lowest mean value for surface roughness followed by varnish group while the maximum increase in surface roughness belonged to the control group of deionized water. Conclusions: Silver diamine fluoride solution was a significantly better than fluoride varnish in preserving surface characteristics of the enamel of primary dentition.